Mitigasi Risiko Rantai Pasok pada Pasokan Penggunaan BBM di Depo Lokomotif PT KAI Sidotopo - Dzaky, Dzawam; Muhimatul Khoiroh, Siti (SURYA TEKNIKA, 2024)
Risk is a factor that always exists in every sector of life incluidng suppky usage in PT KAI. Based on the results and discussion of this research, the conclusion is that there are 20 risk agents and 20 risk events, of which 4 priority risk agents are lack of control over fuel hoses (A13), inaccurate measuring instruments (A7), Over limit Policy (A2) and lack of clear and measurable coordination (A1). Second, there are 6 mitigation actions, namely Modification of the queue and filling system (P1), Improvement of the train supervision and monitoring system with (P2), Training and coordination staff ( P3), Training of machinists and system machinists and managemen update (P4), Modification of fuel control data with by internet (P5), and Maintenance engginer properly and scheduled ( P6). Where the most effective solutions based on HOR Phase 2 are respectively PA 2, PA 3, PA 4 PA 6, PA 5 and PA 1. Meanwhile based on AHP they are PA 2, PA 1, PA 5, PA 6, PA 3 and PA 4. So the alternative solutions developed are PA 2, PA 3 and PA 4.